Gut microbiome dysbiosis in antibiotic-treated COVID-19 patients is associated with microbial translocation and bacteremia - Bernard-Raichon, Lucie; Venzon, Mericien; Klein, Jon; Axelrad, Jordan E.; Zhang, Chenzhen; Sullivan, Alexis P.; Hussey, Grant A.; Casanovas-Massana, Arnau; Noval, Maria G.; Valero-Jimenez, Ana M.; Gago, Juan; Putzel, Gregory; et al. (Nature communications, 2022)
Although microbial populations in the gut microbiome are associated with COVID-19 severity, a causal impact on patient health has not been established. Here we provide evidence that gut microbiome dysbiosis is associated with translocation of bacteria into the blood during COVID-19, causing life-threatening secondary infections. We first demonstrate SARS-CoV-2 infection induces gut microbiome dysbiosis in mice, which correlated with alterations to Paneth cells and goblet cells, and markers of barrier permeability. Samples collected from 96 COVID-19 patients at two different clinical sites also revealed substantial gut microbiome dysbiosis, including blooms of opportunistic pathogenic bacterial genera known to include antimicrobial-resistant species. Analysis of blood culture results testing for secondary microbial bloodstream infections with paired microbiome data indicates that bacteria may translocate from the gut into the systemic circulation of COVID-19 patients. These results are consistent with a direct role for gut microbiome dysbiosis in enabling dangerous secondary infections during COVID-19. Here, the authors show that SARS-CoV-2 infection causes gut microbiome dysbiosis and gut epithelial cell alterations in a mouse model, and correlate dysbiosis observed in COVID-19 patients with blood stream infections, matching reads of bacterial sequences from stool samples to organisms found in the blood.